Colour contrast enhancement based on bright and dark stretching for Ziehl-Neelsen slide images - Zaleha, Salleh; Mohd Yusoff, Mashor; Mat Noor, N. R.; Shazmin Aniza, Abdul Shukor; Norasmadi, Abdul Rahim; Wahab, A. S W; Md Noor, S. S.; Mohamad Idris, F.; Hasan, H. (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org